2021
DOI: 10.3390/s21103403
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Distribution Adaptation for Metal Oxide Semiconductor Gas Sensor Array Drift Compensation

Abstract: Drift compensation is an important issue for metal oxide semiconductor (MOS) gas sensor arrays. General machine learning methods require constant calibration and a large amount of label gas data. At the same time, recalibration will cause a lot of costs, and label gas is difficult to obtain in practice. In this paper, a novel drift compensation method based on balanced distribution adaptation (BDA) is proposed. First, the BDA drift compensation method can adjust the conditional distribution and marginal distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Liu et al 75 extracted features using Fisher linear discriminant approach for drift compensation which decreases the inter-concentration discrepancy of the feature distribution, resulting in concentration independent features. Balanced distribution adaptation algorithm showed better performance over joint distribution adaptation according to Jiang et al 76 where the marginal and conditional distributions are considered. An earlier article 77 combined simple classifiers with these features, resulting in an improved accuracy.…”
Section: Gas Sensor Data Analysismentioning
confidence: 84%
See 1 more Smart Citation
“…Liu et al 75 extracted features using Fisher linear discriminant approach for drift compensation which decreases the inter-concentration discrepancy of the feature distribution, resulting in concentration independent features. Balanced distribution adaptation algorithm showed better performance over joint distribution adaptation according to Jiang et al 76 where the marginal and conditional distributions are considered. An earlier article 77 combined simple classifiers with these features, resulting in an improved accuracy.…”
Section: Gas Sensor Data Analysismentioning
confidence: 84%
“…KNN provided promising results (when integrated with enhance feature selection algorithms) with an increased accuracy up to 97.5% in a drifted E-nose dataset. 76 It was used alongside balanced distribution adaptation (BDA) optimization of features. In another study, KNN showed promising result in determining the perishable quality of shrimp when used with softmax regressor.…”
Section: Gas Sensor Data Analysismentioning
confidence: 99%
“…However, since there is not enough prior information, these methods usually cannot effectively handle samples that differ significantly from the initial distribution. Adaptive correction methods were applied to drift revision through classifier integration by [25] for the first time in 2012. According to the experiment, an ensemble method based on support vector machine was shown to deal well with sensor drifts and was certificated to fulfill the task better than baseline competing method.…”
Section: Drift Correction Methodsmentioning
confidence: 99%
“…Domain adaptation and transfer learning approaches [26][27][28] focus on removing the influence of cross-domain sensitivity to make the prediction model more robust. The balanced distribution adaptor drift compensation method improved the accuracy of drift compensation by reducing the discrepancy between the two domains, as it can adjust the conditional and marginal distributions between the two domains through a weight balancing factor [25]. Additionally, to correct for drift and device variation, a transfer learning-based drift correction autoencoder model for adaptive domain adaptation was proposed [29].…”
Section: Drift Correction Methodsmentioning
confidence: 99%
“…Furthermore, component‐correction methods are used to identify and eliminate drift‐sensitive components before building the model. However, owing to a lack of prior information, such methods are generally incapable of processing drifted samples that deviate significantly from the initial distribution 15,21 …”
Section: Related Workmentioning
confidence: 99%